Diagnostics of care about environment: A systematic review through nursing taxonomies - Alexandra González Aguña; Marta Fernández Batalla; Enrique Monsalvo San Macario; Juan Antonio Sarrión Bravo; María Lourdes Jiménez Rodríguez; José María Santamaría García (Wiley, 2021)
Abstract Aim To analyse the representation of the environment in nursing diagnostic taxonomies. Design Systematic scoping review through nursing taxonomies. Methods The first phase identified nursing diagnostic taxonomies by systematic review. The diagnoses were associated with the environment by analysis of terms into the diagnosis label and definition. Data analysis was quantitative with frequency measurements. The second phase mapped the identified diagnoses to establish equivalences using analysis by terms in the diagnostic labels. Finally, the findings obtained in the first phase were compared with the OMAHA System. Results The bibliographic search identified 112 studies and 16 standardized languages for diagnoses. NANDA‐I and ICNP were the most frequent taxonomies; ATIC, the most recent; and OMAHA, the oldest. 2,062 diagnoses from four diagnostic taxonomies were analysed, and 361 associations corresponding to 352 environmental diagnoses were identified. All taxonomies included the environment but with different weight relative to the interpersonal and geopolitical category.